2016
DOI: 10.12973/eurasia.2016.1250a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Learning on Grade 12 Learners’ Performance in Projectile Motions, South Africa

Abstract: The study explored the effect of cooperative learning on Grade 12 learners' performance in projectile motions. A quasi-experimental research design with non-equivalent control group was used. Two schools were purposively selected from Maleboho Central circuit in South Africa based on their performance in Physical Sciences Grade 12 results of 2011. The sample consisted of 49 learners from two schools. School A was used as the Experimental Group (EG) and was taught using cooperative learning technique while scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
(9 reference statements)
1
6
0
7
Order By: Relevance
“…More than 85% students of the treatment group reported that cooperative learning activities were helpful to them in making new friends and studying biology in the group was very much interesting. e results of the present study can be explained in light of the findings of Kibirige and Lehong [26], and they suggested that performance and motivation of learners improve when cooperative learning is used in the science classroom. During cooperative learning activities, group members help each other to learn because they care about the group and their fellow members and derive the benefits of group membership [41].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…More than 85% students of the treatment group reported that cooperative learning activities were helpful to them in making new friends and studying biology in the group was very much interesting. e results of the present study can be explained in light of the findings of Kibirige and Lehong [26], and they suggested that performance and motivation of learners improve when cooperative learning is used in the science classroom. During cooperative learning activities, group members help each other to learn because they care about the group and their fellow members and derive the benefits of group membership [41].…”
Section: Discussionsupporting
confidence: 60%
“…Pandey and Kishore [25] suggested that cooperative learning is effective than the traditional method only at the knowledge level but had no significant effect at the comprehension level at secondary students. Kirbirige and Lehong [26] and Anderson et al [27] reported that cooperative learning enhances performance in science more than traditional methods at the secondary level. Research works of Muraya and Kimamo [28], Achor et al [2], and Nnorom [29] confirm that the cooperative learning strategy (CLS) fostered the learning of biology.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…On the use of new teaching techniques, approximately half of the teachers used new techniques with the students; however, the experimental group of teachers, in the open section of the questionnaire related to use of other techniques, stated that they used both the Jiangsu technique and the group discussion network because they were encouraged to use cooperative teaching. In the findings of a study by Kibirige and Lehong (2016), their results showed that the experimental group outperformed the control group, suggesting that cooperative learning techniques enhanced learners' performance more than the traditional teaching approach. Also, data related to the predominating relationships found between students in our research, the experimental group of teachers were shown to have the highest value of cultivating collaborative relationships between students compared to the control group (48% vs. 40%).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in bakarajosamo, students are trained in the cultivation of character values in the form of cooperative learning. Cooperative learning in educational research is reported to be a successful pedagogy because students work towards shared goals and are considered useful in science classes to solve problems (Kibirige & Lehong, 2016).…”
Section: Discussionmentioning
confidence: 99%